From management to engagement: An affective teaching approach (2016)
ABSTRACT: This project was carried out at the Institución Educativa Doce de Octubre with a 9th grade English class. Traditional classroom management strategies implemented by my CT led students to respond to a behavioral stimulus to avoid being punished. However, students were not engaged and constantly disrespected each other. Looking for alternatives to the traditional classroom management, I came across affective teaching. It is an alternative which allowed me to move from managing the classroom to engaging students and helping them become agents of change. Teacher’s journals, two interviews with my CT and three student focus groups allowed me to find out the extent to which these affective teaching strategies contributed to student engagement and helped them become agents of changes.